The 2022 focused update of the 2018 Korean Hypertension Society Guidelines for the management of hypertension - Kim, Hack-Lyoung; Lee, Eun Mi; Ahn, Shin Young; Kim, Kwang-il; Kim, Hyeon Chang; Kim, Ju Han; Lee, Hae-Young; Lee, Jang Hoon; Park, Jong-Moo; Cho, Eun Joo; Park, Sungha; Shin, Jinho; et al. (Clinical hypertension, 2023)
Hypertension is the leading cause of death in human being, which shows high prevalence and associated complications that increase the mortality and morbidity. Controlling blood pressure (BP) is very important because it is well known that lowering high BP effectively improves patients’ prognosis. This review aims to provide a focused update of the 2018 Korean Hypertension Society Guidelines for the management of hypertension. The importance of ambulatory BP and home BP monitoring was further emphasized not only for the diagnosis but also for treatment target. By adopting corresponding BPs, the updated guideline recommended out-of-office BP targets for both standard and intensive treatment. Based on the consensus on corresponding BPs and Systolic Blood Pressure Intervention Trial (SPRINT) revisit, the updated guidelines recommended target BP in high-risk patients below 130/80 mmHg and it applies to hypertensive patients with three or more additional cardiovascular risk factors, one or more risk factors with diabetes, or hypertensive patients with subclinical organ damages, coronary or vascular diseases, heart failure, chronic kidney disease with proteinuria, and cerebral lacunar infarction. Cerebral infarction and chronic kidney disease are also high-risk factors for cardiovascular disease. However, due to lack of evidence, the target BP was generally determined at < 140/90 mmHg in patients with those conditions as well as in the elderly. Updated contents regarding the management of hypertension in special situations are also discussed.